PERANCANGAN REAKTOR UNTUK PRODUKSI BIODIESEL GENERASI 2 DARI BIOMASA SAWIT - Maharani Dewi Solikhah; Adi Prismantoko; Adinda Prawitasari; Bina Restituta Barus; Agus Kismanto (Jurnal Teknologi, 2022)
Indonesia has abundance of biomass that underutilized, including oil palm biomass in such as empty fruit bunches and palm fronds. The biomass can be converted into biohydrocarbons through a pyrolysis process that produces bio-oil and followed by an up-grading process to improve its quality. Upgrading Bio-oil into biohydrocarbons can be conducted through various production processes, including hydrothermal processes. Bio-oil has different chacateristic compared to diesel fuel. Bio-oil has a high water content (11-50%), high acidity, and high viscosity (> 40 cP). Based on these characteristics, the hydrothermal process has the advantage of being able to operate with raw materials that have a high water content. The operating conditions of the hydrothermal process are 300 – 400 oC, 150 – 200 bar. For this reason, a bio-oil upgrading reactor was designed using a hydrothermal process to operate at a temperature of 420 oC and a pressure of up to 220 bar.